Античні вагові гирі з монет - Чехович, О.Г. (Археологія і давня історія України, 2020)
Публікується невелика група вагових гир, виготовлених з бронзових монет, що зберігається у фондах Інституту археології НАН України та походять з випадкових знахідок на пам’ятках Північного Причорномор’я. The study of scale weights of the ancient centers of the Northern Pontic region is of greater importance both for the study of metrology, monetary and weight systems of this region, and for understanding the general picture of trade and economic processes in ancient times. This paper presents small-sized weights made of bronze coins that are kept in the Scientific Repository of the Institute of Archaeology of the NAS of Ukraine.